How Using the Herbart Method Affects Sixth Graders' Mathematical Thinking - Karim, Asst.L. Bafrin Gharib Ghafoor; Hassan, Asst.L. Chopi Rauf (Sulaimani Journal for Humanities, 2026)
The aim of this study is to identify the effect of using the Herbart method on developing mathematical thinking among sixth-grade primary school students in the subject of mathematics. To achieve the objectives of the study, the experimental method was used. The requirements of the study were prepared, which included identifying the scientific content, formulating behavioral objectives, preparing daily lesson plans, and then constructing and preparing a mathematical thinking test. The mathematical thinking test consisted of five skills and ten items. After verifying the validity and reliability of the test, both were found to be high and acceptable. The experiment was conducted on (38) students: an experimental group of (19) students and a control group of (19) students from sixth-grade primary students at Ayubi Primary School for the academic year (2025–2026). The two groups were equivalent in terms of students’ age calculated in months, a pre-test of mathematical thinking, Raven’s intelligence test, and previous year grades. The researchers taught the experimental group according to the Herbart method, which includes five steps, while the control group was taught using the traditional method. After the completion of the experiment, the mathematical thinking test was administered to both groups. A number of appropriate statistical tools were used, such as Pearson’s correlation coefficient, arithmetic mean, standard deviation, and the t-test, within the SPSS program. The results showed a statistically significant difference at the significance level (0.05) between the mean scores of the students in the two research groups on the mathematical thinking test, in favor of the experimental group. The study recommends using the Herbart method at the primary level in teaching mathematics and conducting training courses for mathematics teachers at all levels to enhance their knowledge of mathematical thinking and its skills.
Keywords: Herbart method; mathematical thinking